Sensemaking in turbulence : an analysis of the merger of the Central University of Technology from a sensemaking perspective - Marumo, Khomotso Moetanalo Hilda (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2008.